Pengaruh Kompetensi Pedagogik Dosen terhadap Prestasi Akademik Mahasiswa Universitas Patompo - Yunus, Irham Maulana; Aisyah T, A. Indira Nurul (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the influence of lecturers’ pedagogical competencies on students’ level of understanding in Social Studies courses at Patompo University. The research used a quantitative approach with an ex post facto method. The population of the study was 30 students taking Social Studies courses, simultaneously made as a sample by saturation sampling technique. The research instrument took the form of a Likert-scale questionnaire measuring lecturers’ pedagogical competence and students’ level of understanding, complemented by grading documentation. Data were analyzed using simple linear regression and t tests. The results of the study showed that the lecturers’ pedagogical competence positively and significantly affected the students’ level of understanding, with values of R = 0.742 and R2 = 0.513. The t-test resulted in t count = 5.432 t table = 2.048 at α = 0.05, which means the hypothesis was accepted. These findings indicate that improving lecturers’ pedagogical competencies can strengthen students’ understanding of lecture material.